Do students' styles of learning affect how they adapt to learning methods and to the learning environment? - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Objectives: The process of development and evaluation of undergraduate medical education programs should include analysis of learners' characteristics, needs, and perceptions about learning methods. This study aims to evaluate medical students' perceptions about problem-based learning methods and to compare these results with their individual learning styles. Materials and Methods: The survey was conducted at Marmara University Medical School where problem-based learning was implemented in the curriculum for the first three years of the medical education. An evaluative questionnaire about a student-centered learning environment and an Inventory of Learning Styles were completed by the students. One-way ANOVA and Kruskal Wallis tests were used for statistical analyses of the study. Results: It was found that personally interested students who need external regulation strategies and who were prone to learn by stepwise processing were less satisfied with problem-based learning and other active learning methods than students who were less dependent on these learning styles. Thus, the former students did not benefit much from the organization, content, acquired knowledge and skills of problem-based learning. Conclusion: It is important for the students to develop their self-regulated learning skills so that they can benefit from problem-based learning and student-centered learning activities. Curriculum development and program evaluation studies should consider improving the students' development of self-regulation and professional skills.
Keywords: Medical education; Problem-based learning; Learning styles; Curriculum development; STRATEGIES; PBL